(untitled) - Romaine, Suzanne (New York, 1994)
The book provides an introduction to the field of sociolinguistics, emphasizing the constant interaction between society and language. It discusses both traditional and more recent issues such as language and social class, language and gender, language in education, pidgins and creoles, and language change.
Keywords: Language and languages,Sociolinguistics; Study and teaching,Social aspects